The Effect of the Pyramid Training Method System on Upper Body Climbing Endurance in Boulder Athletes - Ali Husen; Dikdik Zafar Sidik; Sagitarius (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of the pyramid system training method on upper body climbing endurance in bouldering athletes. The need for upper body strength endurance is a crucial component of bouldering performance because climbing activities require intense and repeated isometric and dynamic contractions. This study used a one-group pretest–posttest experimental design involving ten members of the PAMOR FPOK UPI rock climbing division as research subjects. The instrument used to measure strength endurance was the bent arm hang test, which has high validity and reliability in measuring isometric abilities relevant to climbing performance. The treatment in the form of pyramid system training was given for sixteen sessions with progressive load variations focused on the upper body muscles. Data were analyzed using descriptive tests, normality tests, homogeneity tests, and paired sample t-tests. The results showed a significant increase between pretest and posttest scores, as evidenced by a mean improvement of 2.44 seconds in the bent arm hang test (pretest: 23.32 ± 14.00 s; posttest: 25.76 ± 13.45 s), with the paired sample t-test indicating a statistically significant difference (t = −10.584, p < 0.001), thus it can be concluded that the pyramid system training method is effective in improving upper body climbing endurance in bouldering athletes. These findings indicate that training with gradual loads can be used as an alternative training program relevant to the physiological demands of rock climbing, especially bouldering.